Pendekatan Antropologis dalam Studi Islam - M. Dimyati Huda (Sekolah TinggiAgama Islam Negeri (STAIN) Kediri, 2016)
Anthropological approach to understand religion means an attempt to understand religion by looking at the form of religious practices that are growing in society. Anthropology is a discipline that conveys the world view that depends on the scientific perspective, philosophical view, or religious beliefs. With this world view one can understand their own world. By studying anthropology, we can realize the cultural diversity of humankind and its influence in education. Education can be defined as a process of learning, the provision of knowledge, skills and attitudes. Education can be obtained through formal and informal institutions. Teaching culture through informal institutions is done through enculturation in the family environment. Finally, learners are guided to be responsible with all the knowledge they have learned, to live in the society with thier potentials, and control nature for the purpose of pleasing the holy God Almighty.